2022
DOI: 10.1007/s00221-022-06456-x
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of active listening during 3D sound localization

Abstract: In everyday life, sound localization entails more than just the extraction and processing of auditory cues. When determining sound position in three dimensions, the brain also considers the available visual information (e.g., visual cues to sound position) and resolves perceptual ambiguities through active listening behavior (e.g., spontaneous head movements while listening). Here, we examined to what extent spontaneous head movements improve sound localization in 3D—azimuth, elevation, and depth—by comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 67 publications
2
12
0
Order By: Relevance
“…The auditory target was a white-noise (43–22000 Hz; sample rate: 44100 Hz), with an 80% amplitude-modulation at 2.5 Hz. We adopted this broadband stimulus to preserve processing of all frequencies available to each ear (Hofman et al, 1998 ; Savel et al, 2009 ; Gaveau et al, 2022 ; Valzolgher et al, 2022a ). Moreover, we modulate noise's amplitude to facilitate ITD processing by reducing phase ambiguities (Macpherson and Middlebrooks, 2002 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The auditory target was a white-noise (43–22000 Hz; sample rate: 44100 Hz), with an 80% amplitude-modulation at 2.5 Hz. We adopted this broadband stimulus to preserve processing of all frequencies available to each ear (Hofman et al, 1998 ; Savel et al, 2009 ; Gaveau et al, 2022 ; Valzolgher et al, 2022a ). Moreover, we modulate noise's amplitude to facilitate ITD processing by reducing phase ambiguities (Macpherson and Middlebrooks, 2002 ).…”
Section: Methodsmentioning
confidence: 99%
“…Our experimental setup allowed to deliver sounds at pre-determined positions defined in head-centered coordinates at the beginning of each trial. Specifically, the system computed the pre-determined position in 3D space with respect to the center of the head and the interaural axis, and gave the experimenter visual cues (on a dedicated monitor) to guide the loudspeaker to the exact target position with a 5 cm tolerance (see Gaveau et al, 2022 ). The experimenter held the speaker in the target position for sound emission with her hand.…”
Section: Methodsmentioning
confidence: 99%
“…This behavior is spontaneous in the sense that it is reactive to what is happening in the environment. Previous studies on the effects of the head on sound localization have shown that spontaneous head movements improve localization skills in silence (Coudert et al, 2022 ; Gaveau et al, 2022 ; Gessa et al, 2022 ; Wallach, 1948 ). This is true even when the head movements are not spontaneous but requested or guided by the experimenter (Pastore et al, 2018 ; Thurlow et al, 1967 ).…”
Section: Introductionmentioning
confidence: 99%
“…This approach also allowed us to accurately control the available visual information during the task, thus avoiding a priori visual information about the location of the noise that previous studies have shown can modulate the effects (Kopčo et al, 2010 ). In addition, it exploited a flexible solution to control for sound position in each trial based on the VR-guided positioning of the speaker (see Gaveau et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The crucial role played by head movements in sound localization has been shown by several works in literature in the last decades 31 – 34 . The studies of these motor behavioral strategies have been favored by advanced experimental settings permitting the possibilities for active listening with 8 , 9 and without involving acoustic virtual reality 35 , 36 .…”
Section: Introductionmentioning
confidence: 99%